Integrated learning strategy in arts and culture learning - Kusumawati, Heni; Jogjaningrum, Drijastuti; Rusdewanti, Panca Putri; Fu'adi, Fu'adi (FBSB UNY, 2023)
This research aims to determine the creativity of arts and culture teachers in integrating two different aspects of art. Art education has two kinds of concepts: first, art education, which is related to the artistic expression of art, and second, art education, which is related to the direction of education. For this reason, teachers need strategies to be able to optimally actualize and express students' abilities in exploring their talents in the field of art. This research uses qualitative methods through a digital ethnographic approach. Data collection through observation, questionnaires with forms, and documentation. The research results show that creative teachers will have a great sense of curiosity, be open, take initiative, and have high loyalty in carrying out their duties. This cannot be separated from internal and external factors that can encourage teachers to continue to develop themselves. The form of teacher creativity in exploring music, dance, fine art, or theatre material is realized in the form of collaboration between the arts. With these results, it is hoped that Arts and Culture learning can be optimized to develop aesthetic, artistic, critical, appreciative, and creative feelings in students.Keywords: creativity, arts and culture, integrated learning Strategi pembelajaran terpadu dalam pembelajaran seni dan budayaAbstrak Konsep pendidikan seni pada dasarnya ada dua macam yaitu konsep pendidikan seni yang berkaitan dengan aspek ekspresi artistic dan konsep pendidikan seni yang dikaitkan dengan tujuan Pendidikan. Untuk itu diperlukan strategi dari guru agar dapat mengaktualisasikan dan mengekspresikan secara optimal kemampuan peserta didik dalam mengeksplorasi bakatnya di bidang seni. Seorang guru yang kreatif akan memiliki rasa keingintahuan yang besar, bersikap terbuka, inisiatif dan memiliki dedikasi yang tinggi dalam menjalankan tugas. Hal ini tidak lepas dari factor internal dan eksternal yang dapat mendorong guru untuk terus mengembangkan diri. Pembelajaran Seni Budaya diharapan dapat menumbuhkembangkan kepekaan rasa estetik dan artistik, sikap kritis, apresiatif, dan kreatif pada peserta didik, sedangkan bentuk kolaborasi antar aspek seni menjadi pembelajaran terpadu (integrated learning) merupakan bentuk kreativitas guru dalam mengeksplorasi materi seni music/tari/rupa/teater dengan seni yang lain. Tujuan dari penelitian ini adalah mendeskripsikan upaya guru dalam mengembangkan potensi peserta didik pada mata pelajaran Seni Budaya, mendeskripsikan strategi konseptual yang dilakukan guru seni budaya dalam memadukan 2 aspek seni, dan wujud kreativitas guru seni budaya dalam mengintegrasikan 2 aspek seni yang berbeda.Kata kunci: kreativitas, seni dan budaya, pembelajaran terpadu